Evaluation Of Doctors' Adherence To Medication Recommendations Of Clinical Practice Guidelines On Management Of Hypertension (CPG 2008) At Hospital Pulau Pinang - Ahmad, Nafees (2012)
The existing literature suggests that doctors’ divergence from guidelines is one of the major contributing factors for poor control of hypertension. The present research in which 26 doctors were enrolled was cross sectional study conducted at Hospital Pulau Pinang (HPP). Its aim was to evaluate doctors’ knowledge, attitude and practice of Malaysian clinical practice guidelines on the management of hypertension CPG (2008), and factors associated with guidelines’ adherence and hypertension control. Doctors’ knowledge and attitudes on CPG (2008) were evaluated through a questionnaire. Prescriptions written by 26 enrolled doctors to 650 established hypertensive outpatients (25 prescriptions per enrolled doctor with 25% drop out rate) were noted on visit one along with patients’ demographic and clinical data.